Examining projection bias in experimental auctions: the role of hunger and immediate gratification - Teresa Briz; Andreas C. Drichoutis; Lisa House (Agricultural and Food Economics, 2015)
The relevance of projection bias in decision making processes has been widely studied, but not specifically in experimental auctions. We study the role of projection bias in experimental auctions by examining the bidding behavior of hungry and non-hungry subjects on food products delivered either immediately after the auction or in 1 week's time. Results indicate that the difference in bids between a hot state (hunger) and a cold state (satiation) almost doubles when subjects have to predict their future tastes versus when they bid for a product intended for immediate consumption. More specifically, when subjects have to predict their future willingness to pay from their current tastes, they tend to over-predict their hunger and under-predict satiation.
Keywords: 330; Experimental auction; Willingness to pay; Projection bias; Hunger